Visualization of Three Dimensional Vortex Dominated Flows in a Towing Tank - Bueno-Galdo, Jorge (2020)
The present paper describes a series of flow visualization studies, which have been performed in a towing tank and utilize laser ind uced fluorescence as a means of observation. The setup, described herein, has been designed specifically f or visualizing three dimensional vortex dominated flows. Two diff erent projects are being performed currently in this facility. The first one focuses on the development of tip vortices on hydrofoils, and the second on the flow structures behind inclined bodies of revolution. The experimental setup required for both projects, particularly the optical system, is almost identical, and the details are provided in the following section. Brief summaries highlighting some of the results of observations, are provided in the chapters that follow. More detailed information is described by Ward and Katz (1987a,b), and by Francis and Katz (1986).